Vladimir Mayakovski and Demian Biedny: Literature as an Instrument of Propaganda on the Example of Polish–Soviet War 1919–1921 - Ceglarek, Michał (Respectus Philologicus, 2017)
The year 1920 saw the shaping and crystallisation of stylistic and literary-ideological canon regarding the dispute about Bolshevik Russia’s place in European civilisation. The sides of the Polish-Soviet conflict are in possession of a large arsenal of tropes and rhetorical figures, routinely used in printed sources, occasional publications, posters, caricatures, postcards and all kinds of gadgets. Particular attention was dedicated to the creation of massive weapon of “war on paper and canvas”, i.e. to propaganda and ideological proselytism. A propaganda war was imposed upon Poland prior to the armed conflict. The political weapons deployed by the Russia of Lenin and Trotsky – violent agitation and propaganda aimed against the “White Poles” and favouring “Soviet Poland” – significantly supported military efforts and political-diplomatic campaign. The numerous activists and artists engaged in the anti-Polish propaganda of the period included the especially noteworthy Vladimir Mayakovsky, Demian Biedny, Viktor Deni and Izaac Babel. Their bellicose poems and, in the case of the latter, satirical drawings incomparably kindled the will to struggle against the “White Poland”. Soviet propagandists regarded the Polish-Soviet war as a testing ground, with the experiments proving useful for planning future undertakings.
Keywords: propaganda; Polish-Soviet war; Vladimir Mayakovski; Demian Biedny